A nylon composition, a method for preparing the same, and use thereof

CN122878780APending Publication Date: 2026-10-09FUJIAN NANPING NANFU BATTERY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611005544.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

在这种情况下,尼龙材料暴露出两个问题:其一,尼龙分子链中的酰胺键在长期高温及氧气作用下发生断裂,生成羧酸、胺类及低聚物等,这些物质进入电解液后会增加体系水分含量、诱发酸性物质生成,进而腐蚀铝箔集流体并破坏SEI膜稳定性,加速电池容量衰减乃至热失控风险;其二,端基与电解液副反应,尼龙合成过程中残留的端氨基和端羧基在高温下可与六氟磷酸锂发生酸碱反应,生成不溶性磷酸盐沉淀物或可溶性胺盐,既污染电解液又催化尼龙自身的水解或氨解降解,形成恶性循环,从而影响电池使用寿命

Benefits of technology

1.与现有技术相比,本申请通过改性添加剂与云母粉的有机无机杂化改性,显著提升了尼龙组合物的耐腐蚀性能。改性添加剂分子链中引入的全氟癸基长链在填料表面形成紧密的氟原子屏蔽层,赋予材料超疏水特性和极低表面能,有效阻隔电解液中水分及酸性腐蚀介质的侵蚀;同时云母粉经偶联剂有机化改性后,其片状形态在尼龙基体中构建连续的物理屏蔽网络,延长腐蚀介质的扩散路径,而环状碳酸酯基团通过氢键与尼龙酰胺键形成牢固界面结合,避免界面缝隙成为腐蚀通道,使填料均匀分散并发挥骨架增强作用,从而实现化学防护与物理屏蔽的协同效应;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a nylon composition and a preparation method and application thereof, and relates to the technical field of polymer materials. A modified filler is prepared by reacting a coupling agent modified mica powder with a fluorine-containing modified additive and a crosslinking agent. The modified additive is chemically bonded with a fluorine-containing monomer to introduce a fluorocarbon chain segment, and then an epoxy group monomer is used for etherification to construct an epoxy skeleton, and finally, a functional molecule containing a cyclic carbonate structure is obtained through a carbon dioxide cycloaddition. The modified filler forms an organic-inorganic hybrid structure in a nylon matrix, a physical shielding network is constructed by the flaky morphology of the mica powder, the fluorocarbon chain segment endows the material with super-hydrophobic characteristics and low surface energy, and the carbonate group enhances the interfacial compatibility with the nylon matrix through hydrogen bonding. The diisocyanate reacts with the end groups of the nylon to play a role in chain extension and tackiness increase, and the copper salt heat stabilizer and the compounded antioxidant synergistically improve the long-term thermal stability and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of polymer materials, and in particular to a nylon composition, its preparation method, and its application. Background Technology

[0002] As a core component of new energy vehicles and renewable energy storage systems, the safety and lifespan of energy storage batteries directly depend on the reliability of their internal components. Battery sealing rings, as key functional components ensuring the airtightness of the battery cells, have a decisive impact on the overall quality of the battery. Currently, nylon is the mainstream material for battery sealing rings, mainly due to its excellent mechanical strength, good resistance to organic solvents, and mature injection molding process. However, with the continuous improvement of power battery energy density and the continuous extension of the service life of energy storage systems, the operating environment faced by battery sealing rings in actual service is becoming increasingly harsh. Traditional nylon materials can no longer meet the stringent requirements of high-end applications for "long lifespan and low pollution."

[0003] Battery sealing rings must withstand the coupling of multiple complex stresses throughout their entire lifespan. Taking a typical power battery pack as an example, the sealing ring is installed in the sealing groove between the cell top cover and the casing. Its working environment has the following characteristics: First, chemical corrosion. The inner side of the sealing ring is in continuous contact with a carbonate-based organic electrolyte containing lithium hexafluorophosphate. This electrolyte is highly polar and contains trace amounts of water and free acid. Second, severe temperature fluctuations. During the charge and discharge cycles, due to the accumulation of Joule heat and chemical reaction heat, the local temperature of the sealing ring remains in a high-temperature range for a long time. In summer high-temperature environments or under high-rate fast charging, the peak temperature rises for a short period of time. Third, continuous mechanical stress. The sealing ring needs to maintain a constant rebound sealing force under pre-compression to offset the internal pressure changes caused by cell gas production and the stress relaxation caused by material creep. Fourth, a long time span. The design life of power batteries aims for a longer service life, which means that the sealing ring needs to maintain stable performance for tens of thousands of hours under the above harsh conditions. In this context, nylon materials exhibit two problems: First, the amide bonds in the nylon molecular chain break under long-term high temperature and oxygen exposure, generating carboxylic acids, amines, and oligomers. These substances, once introduced into the electrolyte, increase the system's moisture content, induce the formation of acidic substances, and subsequently corrode the aluminum foil current collector and damage the stability of the SEI film, accelerating battery capacity decay and even increasing the risk of thermal runaway. Second, end groups react with the electrolyte. Residual terminal amino and carboxyl groups from the nylon synthesis process can undergo acid-base reactions with lithium hexafluorophosphate at high temperatures, generating insoluble phosphate precipitates or soluble amine salts. This not only contaminates the electrolyte but also catalyzes the hydrolysis or ammonolysis degradation of nylon itself, creating a vicious cycle that affects battery lifespan. Summary of the Invention

[0004] The purpose of this application is to provide a nylon composition, its preparation method, and its application. The nylon composition prepared by this method has excellent corrosion resistance and long-term thermal stability.

[0005] Firstly, the nylon composition provided in this application adopts the following technical solution: A nylon composition comprising the following raw materials in parts by weight: 70-95 parts nylon, 0.1-0.5 parts copper salt heat stabilizer, 0.2-1 parts hindered phenolic antioxidant, 0.2-1 parts phosphite antioxidant, 0.2-3 parts diisocyanate, 0.2-1 parts lubricant, and 5-12 parts modified filler; The modified filler comprises the following raw materials in parts by weight: 1-2 parts coupling agent, 90-110 parts mica powder, 0.5-2 parts crosslinking agent, and 10-20 parts modifying additive; The modified additive is prepared by introducing a fluorocarbon chain, etherifying to construct an epoxy skeleton, and adding to obtain a carbonate.

[0006] By adopting the above technical solution, nylon is used as the matrix material, combined with copper salt heat stabilizers, hindered phenolic antioxidants, phosphite antioxidants, diisocyanates, lubricants, and modified fillers to form a nylon composition. The synergistic effect of these components results in excellent performance in terms of thermal stability, mechanical properties, weather resistance, and corrosion resistance. Specifically, the copper salt heat stabilizer effectively captures free radicals generated during high-temperature processing and long-term use of nylon, inhibiting thermal oxidative degradation reactions and significantly improving the material's thermal stability and upper limit of long-term service temperature. The hindered phenolic antioxidant and phosphite antioxidant are used in combination; the former acts as the primary antioxidant by providing hydrogen atoms to interrupt chain oxidation reactions, while the latter acts as an auxiliary antioxidant to decompose hydrogen peroxides. Together, they form a highly efficient antioxidant system. The introduction of diisocyanate can react with the amino or carboxyl groups at the ends of the nylon molecular chains, playing a role in chain extension and thickening, increasing molecular weight and improving melt strength, while also enhancing the material's mechanical properties and solvent resistance. The modified filler uses mica powder as a matrix. After surface modification with a coupling agent, it reacts with modifying additives and crosslinking agents to form an organic-inorganic hybrid structure. The sheet-like morphology of the mica powder constructs a shielding network within the matrix, effectively blocking the penetration path of corrosive media. The fluorocarbon segments in the modifying additives endow the material with superhydrophobic properties and low surface energy, reducing its sensitivity to moisture. The carbonate groups enhance interfacial compatibility by forming hydrogen bonds with nylon amide bonds, ensuring uniform dispersion of the filler and acting as a reinforcing skeleton. The crosslinking agent promotes chemical bonding between the modifying additives and the mica powder surface, ensuring a firm adhesion of the functional layer. This modified filler not only improves the corrosion resistance and temperature resistance of the composition but also significantly reduces water absorption through a synergistic mechanism of physical shielding and chemical protection, while maintaining excellent mechanical strength and dimensional stability.

[0007] Optionally, the modified additive is prepared by the following method: S1. Mix diethanolamine, fluorinated monomer and anhydrous ethanol, heat under reflux, extract, and distill under reduced pressure to obtain the prepolymer; S2. Mix the prepolymer, sodium hydroxide, tetrabutylammonium bromide, toluene and water, stir, heat, add the epoxy-containing monomer, stir, rotary evaporate, wash, extract, rotary evaporate to obtain the intermediate; S3. Mix the intermediate and tetrabutylammonium bromide, pass carbon dioxide through, heat, stir, extract, wash, and distill under reduced pressure to obtain the modified additive.

[0008] By adopting the above technical solution, in the first step, the nitrogen atom in the diethanolamine molecule acts as a nucleophilic center to undergo a nucleophilic addition reaction with the carbon atom of the vinyl group in the perfluorodecyl vinyl ether molecule. Although the weak electron-donating effect of the oxygen atom in the ether bond makes the double bond relatively electron-rich, the addition reaction can still proceed smoothly under the action of the strong nucleophile amine. The reaction is completed under reflux of ethanol and does not require the addition of a long perfluorodecyl chain to be introduced onto the nitrogen atom. At the same time, the two hydroxyl groups of diethanolamine are retained, resulting in a fluorinated hydroxylated prepolymer. This prepolymer has both low surface energy fluorocarbon segments and retains hydroxyl active sites for subsequent reactions. In the second step, the hydroxyl groups in the prepolymer are deprotonated under the action of the alkaline catalyst sodium hydroxide to enhance nucleophilicity. Tetrabutylammonium bromide acts as a catalyst to promote the reaction at the oil-water interface. The hydroxyl groups act as nucleophiles to attack the epoxy ring of the epoxy monomer, causing the epoxy ring to open and form ether bonds. By controlling the ratio of epoxy monomer to hydroxyl groups, some unreacted epoxy groups are retained after the reaction. After the two hydroxyl groups in the prepolymer react with some epoxy groups, the product molecular chain still retains unreacted epoxy groups, forming an intermediate containing fluorocarbon segments, an ether bond backbone, and residual epoxy groups. This not only extends the molecular chain length but also creates conditions for the next step of the reaction. In the third step, under the catalysis of tetrabutylammonium bromide, the residual epoxy group in the intermediate molecule undergoes a cycloaddition reaction with carbon dioxide under heating and pressure, transforming the three-membered epoxy ring into a five-membered cyclic carbonate structure. This reaction utilizes the greenhouse gas CO2 as a raw material, with mild reaction conditions and green chemical characteristics. The resulting modified additive molecule simultaneously contains fluorocarbon segments providing superhydrophobicity and low surface energy, ether bond skeleton providing flexibility, and cyclic carbonate groups interacting with nylon amide groups through hydrogen bonds to enhance interfacial compatibility. This multifunctional molecule is then bridged on the surface of mica powder by coupling agents and cured by crosslinking agents to form an organic-inorganic hybrid modified filler, achieving a synergistic effect of physical shielding and chemical protection.

[0009] Optionally, the modified filler is prepared by the following method: The coupling agent is mixed with solvent and water, mica powder is added, and the mixture is stirred. Modifying additives, anhydrous ethanol, and crosslinking agent are then added, the mixture is heated, and stirred to obtain the modified filler.

[0010] By employing the above technical solution, the coupling agent first chemically bonds with the hydroxyl groups on the surface of mica powder, achieving organic modification of the mica powder and improving its dispersibility in organic media and its reactivity with subsequent components. Subsequently, the added modifying additives, under the action of a crosslinking agent, undergo a ring-opening crosslinking reaction with the surface of the coupling agent-modified mica powder, firmly grafting fluorinated segments and carbonate groups onto the mica powder surface, forming an organic-inorganic hybrid structure. This preparation method features mild reaction conditions, ensuring the complete preservation of the flake-like morphology of the mica powder in the resulting modified filler. This constructs an effective physical shielding network within the nylon matrix. Simultaneously, the surface-grafted fluorocarbon chains reduce the surface energy of the material, and the carbonate groups enhance interfacial compatibility with nylon, resulting in uniform dispersion of the filler and its role in reinforcing the skeleton. This significantly improves the corrosion resistance, temperature resistance, and mechanical properties of the composition.

[0011] Optionally, the mass ratio of the diethanolamine to the fluorinated monomer is 1:(0.8-1.2).

[0012] By employing the above technical solution, the mass ratio of diethanolamine to fluorinated monomer is controlled at 1:(0.8-1.2), a range that balances reaction efficiency and product structure control. An appropriate mass ratio ensures the full reaction of the secondary amine nitrogen atom in diethanolamine, while preventing excessive residue of fluorinated monomer and retaining the two hydroxyl groups in the diethanolamine molecule. This provides sufficient active sites for the subsequent etherification reaction, resulting in a precise and controllable molecular structure of the prepolymer. When the fluorinated monomer is slightly insufficient, it avoids excess monomer residue leading to difficulties in subsequent separation, while retaining an appropriate amount of unreacted hydroxyl groups to provide sufficient active sites for the next etherification reaction, ensuring a precise and controllable molecular structure of the prepolymer.

[0013] Optionally, the mass ratio of the prepolymer, sodium hydroxide, tetrabutylammonium bromide, toluene and water, and epoxy-containing monomer is 1:(1.5-3):(4-8):(300-500):(300-500):(1-2).

[0014] By adopting the above technical solution, the prepolymer, as the core reactant, is used in a reasonable ratio with the epoxy-containing monomers to ensure that the hydroxyl and epoxy groups react fully and to avoid excessive residue of any component. The amount of sodium hydroxide is matched with the mass ratio of the prepolymer, which provides a sufficient alkaline environment and prevents excessive alkali from causing side reactions or product hydrolysis. Tetrabutylammonium bromide is used as a catalyst, and its amount effectively promotes the interfacial reaction between the two phases. Toluene and water form a stable oil-water two-phase system, and this similar mass ratio ensures that the organic phase and the aqueous phase are in full contact, providing a suitable mass transfer environment for the reaction.

[0015] Optionally, the fluorinated monomer is any one or more of perfluorodecyl vinyl ether.

[0016] By adopting the above technical solution, the fluorinated monomer is selected as perfluorodecyl vinyl ether, which contains long-chain perfluoroalkyl and vinyl ether reactive groups in its molecule. The perfluorodecyl group has extremely high fluorine content and a tight fluorine atom shielding layer, which endows the material with excellent superhydrophobicity and chemical corrosion resistance, effectively blocking the erosion of water and corrosive media. The vinyl ether group has moderate reactivity and can chemically bond with the amino group of diethanolamine. At the same time, the introduction of the perfluoro long chain significantly reduces the surface energy of the material.

[0017] Optionally, the epoxy-containing monomer is any one or more of glycidyl methacrylate and epichlorohydrin.

[0018] By employing the above technical solution, the methacrylate groups provide reaction sites for possible subsequent free radical polymerization or further functionalization, and the post-reaction product is halogen-free, making it more environmentally friendly. The epoxy groups can undergo ring-opening etherification with the hydroxyl groups in the prepolymer to construct an epoxy backbone, and the post-reaction product is halogen-free, making it even more environmentally friendly. Epichlorohydrin has a simple structure and high reactivity; the introduction of bromine atoms can provide an additional nucleophilic substitution pathway in the ring-opening reaction, improving reaction efficiency. Simultaneously, bromine imparts a certain flame-retardant effect to the material.

[0019] Optionally, the coupling agent is any one of isopropyltris(dioctylpyrophosphate)titanate and 3-(2,3-epoxypropoxy)propyltrimethoxysilane.

[0020] By adopting the above technical solutions, isopropyltris(dioctylpyrophosphate)titanate, with titanium atoms at its center, exhibits high tolerance to water-containing fillers and excellent hydrolysis resistance due to its pyrophosphate groups. It can form stable chemical bonds with various hydroxyl groups on the surface of mica powder, while the long-chain alkyl groups improve compatibility with the nylon matrix and possess flame retardant properties. 3-(2,3-epoxypropoxy)propyltrimethoxysilane, with silicon atoms at its center, forms silanol bonds after methoxy hydrolysis, which condense with hydroxyl groups on the surface of mica powder. The epoxy groups can then directly chemically bond with amino groups in subsequent crosslinking agents or modifying additives.

[0021] Secondly, the method for preparing a nylon composition provided in this application adopts the following technical solution: A method for preparing a nylon composition includes the following steps: The nylon was dried, and copper salt heat stabilizer, hindered phenol antioxidant, phosphite antioxidant, diisocyanate, lubricant, and modified filler were added. The mixture was stirred, melt-extruded, and granulated to obtain a nylon composition.

[0022] By adopting the above technical solution, the nylon composition is prepared by melt blending. First, the nylon is thoroughly dried to remove moisture and avoid degradation during high-temperature processing. Then, each component is added in proportion and stirred for premixing, so that the copper salt heat stabilizer, antioxidant and other additives and modified fillers are uniformly dispersed. Then, it is melt-extruded and granulated by twin-screw extruder. This preparation method uses the shearing action of the screw to achieve efficient dispersion and interfacial fusion of each component. The fluorocarbon chain and cyclic carbonate groups in the modified filler form good compatibility with the nylon matrix.

[0023] In summary, this application includes at least one of the following beneficial technical effects: 1. Compared with existing technologies, this application significantly improves the corrosion resistance of nylon compositions through organic-inorganic hybrid modification of modified additives and mica powder. The perfluorodecyl long chains introduced into the molecular chain of the modified additive form a dense fluorine atom shielding layer on the filler surface, endowing the material with superhydrophobic properties and extremely low surface energy, effectively blocking the erosion of water and acidic corrosive media in the electrolyte; at the same time, after organic modification by coupling agent, the sheet-like morphology of mica powder constructs a continuous physical shielding network in the nylon matrix, extending the diffusion path of corrosive media, while the cyclic carbonate groups form a strong interfacial bond with the nylon amide bonds through hydrogen bonds, preventing interfacial gaps from becoming corrosion channels, so that the filler is uniformly dispersed and plays a skeletal reinforcement role, thereby achieving a synergistic effect of chemical protection and physical shielding; 2. Compared with the prior art, this application endows the nylon composition with excellent long-term thermal stability through the synergistic effect of copper salt heat stabilizers, compound antioxidants, and diisocyanates. Copper salt heat stabilizers can effectively capture free radicals generated during high-temperature processing and long-term use, inhibiting the thermal oxidative degradation reaction of the nylon molecular chains; the hindered phenolic primary antioxidant and the phosphite secondary antioxidant are compounded to form a highly efficient antioxidant system, with the former interrupting the chain oxidation reaction by providing hydrogen atoms, and the latter decomposing hydrogen peroxide to block the autocatalytic cycle; diisocyanate reacts with the terminal amino and carboxyl groups of nylon to achieve chain extension and thickening, improving melt strength. Detailed Implementation

[0024] Unless otherwise specified, the parameters and sources of the specific chemical substances used in the embodiments and comparative examples of this application are all commercially available products. Hindered phenolic antioxidant, Irganox 1010, BASF; Copper salt heat stabilizer, model: BYK-MAX HS 4300, BYK; Phosphite antioxidant, model: Irgafos 168, BASF; Lubricant, model: Licomont CaV 102, BASF; The nylon is nylon 66; Mica powder, 1250 mesh, Jiyesheng.

[0025] Example 1 A method for preparing a nylon composition includes the following steps: The first step is to prepare the modified additives. 0.1 parts by weight of diethanolamine, 0.1 parts by weight of perfluorodecyl vinyl ether, and 200 parts by weight of anhydrous ethanol were mixed to obtain a first mixture. The first mixture was refluxed at 80°C for 10 h to obtain a second mixture. The second mixture was extracted with water to remove unreacted diethanolamine, and then distilled under reduced pressure at 0.08 MPa for 1 h to remove ethanol and residual water, yielding a prepolymer.

[0026] 0.1 parts by weight of prepolymer, 0.2 parts by weight of sodium hydroxide, 0.6 parts by weight of tetrabutylammonium bromide, 50 parts by weight of toluene, and 50 parts by weight of deionized water were mixed and stirred at 300 rpm for 30 min. The mixture was then heated to 55 °C to obtain a third mixture. 0.19 parts by weight of glycidyl methacrylate were added to the third mixture, and the mixture was stirred at 300 rpm for 9 h to obtain a fourth mixture. The fourth mixture was rotary evaporated for 1 h to remove toluene. The rotary evaporated product was washed once with water, and the organic phase was extracted with dichloromethane to separate the organic phase. The organic phase was then rotary evaporated for another 1 h to remove dichloromethane, yielding an intermediate.

[0027] The intermediate and 0.64 parts by weight of tetrabutylammonium bromide were added to a high-pressure reactor, and carbon dioxide was introduced. The reaction temperature was controlled at 135°C and the carbon dioxide pressure at 0.6 MPa. The mixture was stirred at 300 rpm for 48 hours to obtain the fifth mixture. After the reactor was cooled to 25°C and depressurized, the fifth mixture was transferred to an extraction apparatus and extracted once with ethyl acetate. The mixture was then washed twice with water to obtain the organic layer. The organic layer was distilled under reduced pressure at 0.08 MPa for 2 hours to obtain the modified additive.

[0028] The second step is to prepare the modified filler. 56 parts by weight of anhydrous ethanol and 24 parts by weight of water were mixed to obtain an ethanol-water solution. 1 part by weight of 3-(2,3-epoxypropoxy)propyltrimethoxysilane was mixed with the ethanol-water solution, and 90 parts by weight of mica powder were added. The mixture was stirred at 300 rpm for 5 hours at 65°C to obtain a sixth mixture. 10 parts by weight of a modifying additive, 110 parts by weight of anhydrous ethanol, and 0.5 parts by weight of isophorone diamine (crosslinking agent) were added to the sixth mixture, and the mixture was heated to 90°C and stirred at 300 rpm for 9 hours to obtain the modified filler.

[0029] 80 parts by weight of nylon were dried in an oven at 105°C for 12 hours. Then, 0.2 parts by weight of copper salt heat stabilizer, 0.5 parts by weight of hindered phenolic antioxidant, 0.3 parts by weight of phosphite antioxidant, 1 part by weight of hexamethylene diisocyanate (diisocyanate), 0.5 parts by weight of lubricant, and 10 parts by weight of modified filler were added. The mixture was stirred at 300 rpm for 30 minutes at room temperature in a high-speed mixer. The mixture was then transferred to an internal mixer where the temperature was raised to 270°C, the speed was adjusted to 100 rpm, and the mixture was stirred for 10 minutes to melt. The melt was then transferred to a twin-screw extruder and extruded and granulated at 275°C to obtain the nylon composition. The prepared nylon composition was then injection molded to obtain battery sealing rings. Example 2

[0030] The difference between Example 2 and Example 1 is that 1 part by weight of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 90 parts by weight of mica powder, 10 parts by weight of modifying additive, and 0.5 parts by weight of isophorone diamine in Example 1 are replaced with 1.5 parts by weight of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 100 parts by weight of mica powder, 10 parts by weight of modifying additive, and 1.2 parts by weight of isophorone diamine. Example 3

[0031] The difference between Example 3 and Example 1 is that 1 part by weight of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 90 parts by weight of mica powder, 10 parts by weight of modified additive, and 0.5 parts by weight of isophorone diamine in Example 1 are replaced with 2 parts by weight of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 110 parts by weight of mica powder, 20 parts by weight of modified additive, and 2 parts by weight of isophorone diamine. Example 4

[0032] The difference between Example 4 and Example 2 is that in Example 2, 0.1 parts by weight of prepolymer, 0.2 parts by weight of sodium hydroxide, 0.6 parts by weight of tetrabutylammonium bromide, 50 parts by weight of toluene, 50 parts by weight of deionized water, and 0.19 parts by weight of glycidyl methacrylate are replaced with 0.14 parts by weight of prepolymer, 0.27 parts by weight of sodium hydroxide, 0.67 parts by weight of tetrabutylammonium bromide, 53 parts by weight of toluene, 53 parts by weight of deionized water, and 0.2 parts by weight of glycidyl methacrylate. Example 5

[0033] The difference between Example 5 and Example 2 is that in Example 2, 0.1 parts by weight of prepolymer, 0.2 parts by weight of sodium hydroxide, 0.6 parts by weight of tetrabutylammonium bromide, 50 parts by weight of toluene, 50 parts by weight of deionized water, and 0.19 parts by weight of glycidyl methacrylate are replaced with 0.18 parts by weight of prepolymer, 0.32 parts by weight of sodium hydroxide, 0.72 parts by weight of tetrabutylammonium bromide, 56 parts by weight of toluene, 56 parts by weight of deionized water, and 0.2 parts by weight of glycidyl methacrylate. Example 6

[0034] The difference between Example 6 and Example 2 is that in Example 2, 0.1 parts by weight of prepolymer, 0.2 parts by weight of sodium hydroxide, 0.6 parts by weight of tetrabutylammonium bromide, 50 parts by weight of toluene, 50 parts by weight of deionized water, and 0.19 parts by weight of glycidyl methacrylate are replaced with 0.20 parts by weight of prepolymer, 0.40 parts by weight of sodium hydroxide, 0.80 parts by weight of tetrabutylammonium bromide, 60 parts by weight of toluene, 60 parts by weight of deionized water, and 0.2 parts by weight of glycidyl methacrylate. Comparative Example 1

[0035] The difference between Comparative Example 1 and Example 1 is that 1 part by weight of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 90 parts by weight of mica powder, 10 parts by weight of modifying additive, and 0.5 parts by weight of isophorone diamine in Example 1 are replaced with 0.5 parts by weight of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 105 parts by weight of mica powder, 12 parts by weight of modifying additive, and 1 part by weight of isophorone diamine. Comparative Example 2

[0036] The difference between Comparative Example 2 and Example 2 is that in Example 2, 0.1 parts by weight of prepolymer, 0.2 parts by weight of sodium hydroxide, 0.6 parts by weight of tetrabutylammonium bromide, 50 parts by weight of toluene, 50 parts by weight of deionized water, and 0.19 parts by weight of glycidyl methacrylate are replaced with 0.25 parts by weight of prepolymer, 0.40 parts by weight of sodium hydroxide, 0.85 parts by weight of tetrabutylammonium bromide, 75 parts by weight of toluene, 60 parts by weight of deionized water, and 0.2 parts by weight of glycidyl methacrylate. Comparative Example 3

[0037] The difference between Comparative Example 3 and Comparative Example 2 is that 10 parts by weight of modified filler in Example 2 were replaced with 10 parts by weight of mica powder.

[0038] Test case Corrosion resistance: The samples prepared in Examples 1-6 and Comparative Examples 1-3 were placed in a simulated electrolyte (1M LiPF6 dissolved in a mixed solvent of ethylene carbonate and dimethyl carbonate, volume ratio 1:1) and immersed at 60°C for 30 days. The volume expansion rate (%) of the samples was tested. The test results are shown in Table 1.

[0039] Bending strength: The battery sealing rings prepared in Examples 1-6 and Comparative Examples 1-3 were tested according to GB / T 9341-2008 "Determination of bending properties of plastics" at a test rate of 10 mm / min. The test results are shown in Table 1.

[0040] Notched impact strength: The notched impact strength of nylon material was determined according to GB / T 1043-2008 "Determination of impact strength of simply supported plastic beams". The test results are shown in Table 1.

[0041]

[0042] By observing the test data in Table 1, Examples 1-3 and Comparative Example 1 were compared and analyzed. In Examples 1-3, the amount of coupling agent used in the modified fillers was within the range of 1-2 parts by weight, which could fully react with the hydroxyl groups on the surface of mica powder to form a dense organic layer on the surface of mica powder. This provided sufficient active sites for the subsequent grafting of modified additives. The crosslinking agent, within an appropriate range, promoted the ring-opening crosslinking reaction between the modified additives and the surface of the mica powder modified by the coupling agent, so that the fluorinated segments and carbonate groups were firmly bonded to the filler surface, forming a structurally complete organic-inorganic hybrid system. In this hybrid structure, the plate-like morphology of mica powder constructs a continuous physical shielding network in the nylon matrix, effectively extending the diffusion path of corrosive media. At the same time, the fluorocarbon chains grafted on the surface significantly reduce the surface energy of the material, and the carbonate groups enhance the interfacial compatibility through hydrogen bonding with the nylon amide bonds, making the filler uniformly dispersed and undertaking the load transfer function. Therefore, Examples 1-3 showed excellent performance in terms of corrosion resistance and mechanical properties. In Comparative Example 1, the amount of coupling agent used was only 0.5 parts by weight, which was below the lower limit. This resulted in insufficient organication of the mica powder surface, poor compatibility between the large number of exposed inorganic surfaces and the nylon matrix interface, and the inability of modified additives to be effectively grafted onto the filler surface. The hybrid structure was incomplete, and the mica powder was prone to agglomeration in the matrix. Microscopic defects and pores were generated at the interface, and corrosive media rapidly penetrated along the defect channels, significantly weakening the shielding effect. At the same time, interface debonding led to a decrease in stress transfer efficiency, and the mechanical properties were significantly inferior to those of the Example.

[0043] Comparative analysis of Examples 2, 4-6, and Comparative Example 2 showed that the ratios of prepolymer to epoxy-containing monomer, sodium hydroxide, tetrabutylammonium bromide, and solvent in these examples were all within specified ranges. This ensured sufficient ring-opening etherification of the hydroxyl and epoxy groups in the prepolymer molecule. Sodium hydroxide provided a suitable alkaline environment to activate the epoxy groups, while tetrabutylammonium bromide acted as a phase transfer catalyst to promote the equilibrium of the interfacial reaction between the two phases. The oil-water system composed of toluene and water ensured sufficient contact between the organic and aqueous phases, making the reaction system controllable and efficient. When the ratio of prepolymer to epoxy-containing monomer was close to the stoichiometry, the epoxy framework was most complete, and the subsequent cycloaddition reaction with carbon dioxide proceeded fully, resulting in the highest content of the cyclic carbonate structure. This structure interacts strongly with the nylon amide groups through hydrogen bonds, enhancing the interfacial bonding between the modified additive and the matrix. At the same time, the fluorinated segments were uniformly distributed on the filler surface, forming a dense hydrophobic barrier. In Comparative Example 2, the amount of prepolymer used far exceeded the scope of the claims, and the ratio of catalyst and solvent was unbalanced, resulting in an overly viscous reaction system. The selectivity of the reaction between the hydroxyl groups and epoxy groups of the prepolymer decreased, producing a large number of branched or cross-linked byproducts. The molecular structure was uncontrollable, the epoxy group conversion rate was low, the subsequent carbonate reaction was insufficient, the content of functional groups in the resulting modified additives was reduced and unevenly distributed, the compatibility with the nylon matrix deteriorated, the surface modification of the filler was incomplete, and the corrosion resistance and mechanical properties were significantly deteriorated.

[0044] Comparative Example 2 and Comparative Example 3 were analyzed. Example 2 used an organic-inorganic hybrid filler formed by surface modification with a coupling agent followed by reaction with a modifying additive and a crosslinking agent. The fluorocarbon segments grafted onto the mica powder surface endowed the filler with low surface energy and superhydrophobic properties, effectively blocking the penetration of corrosive media. The carbonate groups formed a strong interfacial bond with the nylon amide bond through hydrogen bonds, allowing the filler to be uniformly dispersed in the matrix and constructing a continuous physical shielding network. At the same time, good interfacial compatibility ensured that stress was effectively transferred to the filler skeleton under external force. In contrast, Comparative Example 3 directly used unmodified mica powder. The inorganic surface polarity differed significantly from that of the nylon matrix, resulting in a large number of micropores and defects at the interface. Corrosive media rapidly diffused and penetrated along the interfacial gaps, causing the shielding function to be lost. At the same time, interfacial debonding became a crack initiation source under stress, and stress concentration led to premature material failure and a significant decrease in mechanical properties.

[0045] The above are all preferred embodiments of this application, and are not intended to limit the scope of protection of this application. Therefore, all equivalent changes made to the structure, shape and principle of this application should be covered within the scope of protection of this application.

Claims

1. A nylon composition, characterized in that, The raw materials include the following parts by weight: 70-95 parts nylon, 0.1-0.5 parts copper salt heat stabilizer, 0.2-1 parts hindered phenolic antioxidant, 0.2-1 parts phosphite antioxidant, 0.2-3 parts diisocyanate, 0.2-1 parts lubricant, and 5-12 parts modified filler; The modified filler comprises the following raw materials in parts by weight: 1-2 parts coupling agent, 90-110 parts mica powder, 0.5-2 parts crosslinking agent, and 10-20 parts modifying additive; the modifying additive is prepared by introducing fluorocarbon chains, etherifying to construct an epoxy skeleton, and adding to obtain carbonate.

2. The nylon composition according to claim 1, characterized in that, The modified additive is prepared by the following method: S1. Mix diethanolamine, fluorinated monomer and anhydrous ethanol, heat under reflux, extract, and distill under reduced pressure to obtain the prepolymer; S2. Mix the prepolymer, sodium hydroxide, tetrabutylammonium bromide, toluene and water, stir, heat, add the epoxy-containing monomer, stir, rotary evaporate, wash, extract, rotary evaporate to obtain the intermediate; S3. Mix the intermediate and tetrabutylammonium bromide, pass carbon dioxide through, heat, stir, extract, wash, and distill under reduced pressure to obtain the modified additive.

3. The nylon composition according to claim 1, characterized in that, The modified filler is prepared by the following method: The coupling agent is mixed with solvent and water, mica powder is added, and the mixture is stirred. Modifying additives, anhydrous ethanol, and crosslinking agent are added, the mixture is heated, and stirred to obtain the modified filler.

4. The nylon composition according to claim 2, characterized in that, The mass ratio of the diethanolamine to the fluorinated monomer is 1:(0.8-1.2).

5. The nylon composition according to claim 2, characterized in that, The mass ratio of the prepolymer, sodium hydroxide, tetrabutylammonium bromide, toluene and water, and epoxy-containing monomer is 1:(1.5-3):(4-8):(300-500):(300-500):(1-2).

6. The nylon composition according to claim 2, characterized in that, The fluorinated monomer is any one or more of perfluorodecyl vinyl ether and hexafluorobutyl methacrylate.

7. The nylon composition according to claim 2, characterized in that, The epoxy-containing monomer is any one or more of glycidyl methacrylate and epichlorohydrin.

8. The nylon composition according to claim 3, characterized in that, The coupling agent is any one of isopropyltris(dioctylpyrophosphate)titanate and 3-(2,3-epoxypropoxy)propyltrimethoxysilane.

9. A method for preparing a nylon composition according to any one of claims 1-8, characterized in that, Includes the following steps: The nylon was dried, and copper salt heat stabilizer, hindered phenol antioxidant, phosphite antioxidant, diisocyanate, lubricant, and modified filler were added. The mixture was stirred, melt-extruded, and granulated to obtain a nylon composition.

10. The use of a nylon composition according to any one of claims 1-8 in a battery sealing ring.